2018
DOI: 10.1103/physrevfluids.3.013302
|View full text |Cite
|
Sign up to set email alerts
|

Steady displacement of long gas bubbles in channels and tubes filled by a Bingham fluid

Abstract: Bingham fluids behave like solids below a von Mises stress threshold, the yield stress, while above it they behave like Newtonian fluids. They are characterized by a dimensionless parameter, Bingham number (Bn), which is the ratio of the yield stress to a characteristic viscous stress. In this study, the non-inertial steady motion of a finite size gas bubble in both a plane 2D channel and an axi-symmetric tube filled by a Bingham fluid has been studied numerically. The Bingham number, Bn, is in the range 0 ≤ B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Turning to viscoplastic flows with applications in airway modelling, Craster & Matar (2000) modelled surfactant-driven flow on a single-layer or two-layer film of viscoplastic or Newtonian fluids, showing that, at least in the single-layer case, yield stress decreases spreading rates and can cause the layer to become frozen in a non-trivial static shape. Modelling of propagation of viscoplastic liquid plugs in tubes and channels has shown that increasing the yield stress increases the stress applied to the wall and increases the thickness of the layer of liquid left behind as a plug propagates (Zamankhan et al 2012;Zamankhan, Takayama & Grotberg 2018). Rupture of viscoplastic liquid plugs has also been modelled both experimentally (Hu et al 2015) and numerically (Hu, Romanò & Grotberg 2020), showing that increased yield stress can inhibit plug rupture because a larger pressure drop is required across the plug to make it yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Turning to viscoplastic flows with applications in airway modelling, Craster & Matar (2000) modelled surfactant-driven flow on a single-layer or two-layer film of viscoplastic or Newtonian fluids, showing that, at least in the single-layer case, yield stress decreases spreading rates and can cause the layer to become frozen in a non-trivial static shape. Modelling of propagation of viscoplastic liquid plugs in tubes and channels has shown that increasing the yield stress increases the stress applied to the wall and increases the thickness of the layer of liquid left behind as a plug propagates (Zamankhan et al 2012;Zamankhan, Takayama & Grotberg 2018). Rupture of viscoplastic liquid plugs has also been modelled both experimentally (Hu et al 2015) and numerically (Hu, Romanò & Grotberg 2020), showing that increased yield stress can inhibit plug rupture because a larger pressure drop is required across the plug to make it yield.…”
Section: Introductionmentioning
confidence: 99%
“…Modelling of propagation of viscoplastic liquid plugs in tubes and channels has shown that increasing the yield stress increases the stress applied to the wall and increases the thickness of the layer of liquid left behind as a plug propagates (Zamankhan et al. 2012; Zamankhan, Takayama & Grotberg 2018). Rupture of viscoplastic liquid plugs has also been modelled both experimentally (Hu et al.…”
Section: Introductionmentioning
confidence: 99%
“…For normal breathing conditions of tidal volume equal to 500 ml and 12 breaths/min, typical small reopening velocities are studied in the literature range from 1 mm/s to 10 mm/s. 13 Assuming the fluid viscosity and air–liquid surface tension as 47 cP and 72 dyn/cm, respectively, the corresponding Re, Ca, and Bo are then given by 3.2 1 0.1 6.5 1 6.5 1 and 3.1 1 3.4 1 However, for lung fluids, having surface tension much lower than 72 dyn/cm 12 would lead to larger Ca and Bo values. 15 To investigate all these possible Ca and Bo values that may exist in the human lungs, inertial effects were neglected, and about baseline conditions (i.e., Ca = 0.06 and Bo = 0.003), parameter independent variation studies were then performed for a range of Ca and Bo values.…”
Section: Problem Statementmentioning
confidence: 99%
“…2015; Lopez, Naccache & de Souza Mendes 2018) and bubbles moving inside tubes filled with viscoplastic fluids (Jalaal & Balmforth 2016; Laborie et al. 2017; Zamankhan, Takayama & Grotberg 2018). We will show that the introduction of non-Newtonian properties can significantly influence the bursting behaviour of bubbles on a free surface.…”
Section: Introductionmentioning
confidence: 99%